If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -21 = x + 31 Reorder the terms: -21 + 5x = x + 31 Reorder the terms: -21 + 5x = 31 + x Solving -21 + 5x = 31 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -21 + 5x + -1x = 31 + x + -1x Combine like terms: 5x + -1x = 4x -21 + 4x = 31 + x + -1x Combine like terms: x + -1x = 0 -21 + 4x = 31 + 0 -21 + 4x = 31 Add '21' to each side of the equation. -21 + 21 + 4x = 31 + 21 Combine like terms: -21 + 21 = 0 0 + 4x = 31 + 21 4x = 31 + 21 Combine like terms: 31 + 21 = 52 4x = 52 Divide each side by '4'. x = 13 Simplifying x = 13
| 39=8x-(2x-3) | | 18-4e=e+3 | | 5r-(2r+18)=16 | | -2(2+3x)=-28+6x | | -2a+7-3(-9-4a)= | | -17-2x=9+t | | 7x=--6 | | -.6a=2 | | r+12= | | dfghj=k | | 7n+6n+-5=4n+4 | | 4+2m=6+2m | | 4d+2(7+-2)= | | -1.6=x+1.1 | | 5x-2-x=30 | | c-33+2=443 | | 5-3=43 | | 6z-19-z+4=0 | | 4x+2x+3=9 | | (-4x^2+3x-1)-(4x+2)= | | 4.3=b-1 | | -8+5x-7x=-16 | | 5.16-p=15.48 | | 12-2c+6c= | | 12-22x= | | 0.75(-6)-6= | | 4r-r= | | 3x+9=44-3x | | 29+n=-(-5n-5) | | 7(2+w)=6(w-9) | | 6=2+u | | 2(2x-6)m+2(x+3)m=26 |